2017
DOI: 10.1074/jbc.m117.808600
|View full text |Cite
|
Sign up to set email alerts
|

A screen for kinase inhibitors identifies antimicrobial imidazopyridine aminofurazans as specific inhibitors of the Listeria monocytogenes PASTA kinase PrkA

Abstract: Bacterial signaling systems such as protein kinases and quorum sensing have become increasingly attractive targets for the development of novel antimicrobial agents in a time of rising antibiotic resistance. The family of bacterial Penicillin-binding-protein And Serine/Threonine kinase-Associated (PASTA) kinases is of particular interest due to the role of these kinases in regulating resistance to β-lactam antibiotics. As such, small-molecule kinase inhibitors that target PASTA kinases may prove beneficial as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 63 publications
(84 reference statements)
5
58
2
1
Order By: Relevance
“…Intriguingly, and consistent with the known role of PknB in cell wall homeostasis, these inhibitors were able to significantly potentiate the effect of b-lactams in several types of mycobacteria and in the related Nocardia asteroides [236]. This synergistic concept has also been reported for kinase inhibitors of the nonessential L. monocytogenes PrkA and S. aureus Stk1 Hanks kinases [219,223,[237][238][239][240]. In L. monocytogenes, the broad-spectrum kinase inhibitor staurosporine, as well as some more selective repurposed human kinase inhibitors, was seen to inhibit PrkA activity and sensitize cells to b-lactam drugs [219,237].…”
Section: Drugging Bacterial Kinasessupporting
confidence: 78%
See 1 more Smart Citation
“…Intriguingly, and consistent with the known role of PknB in cell wall homeostasis, these inhibitors were able to significantly potentiate the effect of b-lactams in several types of mycobacteria and in the related Nocardia asteroides [236]. This synergistic concept has also been reported for kinase inhibitors of the nonessential L. monocytogenes PrkA and S. aureus Stk1 Hanks kinases [219,223,[237][238][239][240]. In L. monocytogenes, the broad-spectrum kinase inhibitor staurosporine, as well as some more selective repurposed human kinase inhibitors, was seen to inhibit PrkA activity and sensitize cells to b-lactam drugs [219,237].…”
Section: Drugging Bacterial Kinasessupporting
confidence: 78%
“…This synergistic concept has also been reported for kinase inhibitors of the nonessential L. monocytogenes PrkA and S. aureus Stk1 Hanks kinases [219,223,[237][238][239][240]. In L. monocytogenes, the broad-spectrum kinase inhibitor staurosporine, as well as some more selective repurposed human kinase inhibitors, was seen to inhibit PrkA activity and sensitize cells to b-lactam drugs [219,237]. Similarly, several studies have identified Stk1-inhibiting molecules from small-molecule libraries that sensitize MRSA S. aureus strains to b-lactams [223,[238][239][240].…”
Section: Drugging Bacterial Kinasessupporting
confidence: 64%
“…Although modifications may reduce this compound's reactivity and toxicity, further evidence is needed to assess whether it will retain its effectiveness against Mycobacterium tuberculosis. Although YH-8 is reactive and has poor pharmacokinetic properties, several stable non-reactive inhibitors are known for PknB and other related bacterial kinases, including some which were in human trials for other diseases [15][16][17][29][30][31][32][33]. Improving YH-8 by reducing its reactivity and toxicity and incorporating structure-activity relationship data from the aforementioned inhibitors may lead to improvements in the properties of YH-8, leading to a viable clinical lead compound.…”
Section: Discussionmentioning
confidence: 99%
“…Listeria monocytogenes mutants deficient in the PASTA kinase, PrkA, show impaired growth under nutrient-limiting conditions and reduced survival and replication in host cells when compared to the wild-type strain [63]. Moreover, deletion of homologous PASTA kinase in some species, for example L. monocytogenes and S. aureus, has been linked to increased susceptibility to β-lactam antibiotics [64][65][66]. This contrasts the homologous Mycobacterium tuberculosis PASTA kinase, PknB, which is essential for survival [67].…”
Section: Combination Therapy Iii: Inhibits Kinase Activity and Intrinmentioning
confidence: 99%